2020
DOI: 10.3892/ol.2020.12136
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker heterogeneity between primary breast cancer and synchronous axillary lymph node metastases

Abstract: Whether the expression status of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER-2) receptor and Ki-67 show concordance between the primary tumors and the synchronous axillary lymph node (ALN) metastases has been discussed in numerous studies. However, to date, the results of these studies remain controversial. Therefore, the present study aimed to investigate whether the expression of ER, PR, HER-2 and Ki-67 was in concordance between the primary tumors and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Several reports indicate that various molecular biomarkers also demonstrate similar expression status in PT and metastatic lesions. For instance, the concordance rates of expression status in both foci have been found to reach 72.2% for ER, 88.9% for PR, and 90.7% for HER2 ( 52 ); rates of 77.6% for ER (κ = 0.534, p < 0.01), 82.2% for PR (κ = 0.640, p < 0.01), 84.1% for HER2 (κ = 0.647, p < 0.01) have also been reported in Chinese women ( 53 ), and rates of 96.7% for ER/PR (κ = 0.773, κ = 0.654, accordingly) and 90% for HER2 (κ = 0.785) have been recently reported ( 54 ).…”
Section: Discussionmentioning
confidence: 84%
“…Several reports indicate that various molecular biomarkers also demonstrate similar expression status in PT and metastatic lesions. For instance, the concordance rates of expression status in both foci have been found to reach 72.2% for ER, 88.9% for PR, and 90.7% for HER2 ( 52 ); rates of 77.6% for ER (κ = 0.534, p < 0.01), 82.2% for PR (κ = 0.640, p < 0.01), 84.1% for HER2 (κ = 0.647, p < 0.01) have also been reported in Chinese women ( 53 ), and rates of 96.7% for ER/PR (κ = 0.773, κ = 0.654, accordingly) and 90% for HER2 (κ = 0.785) have been recently reported ( 54 ).…”
Section: Discussionmentioning
confidence: 84%
“…Several other studies have already addressed this issue, showing widely variable results spanning from nearly overlapping [29,30] to significantly discordant profiles, sometimes with differences in biomarker status in almost half of the cases [11,14,31]. However, all the aforementioned papers evaluated post-operative specimens, often including patients who had previously received NAC.…”
Section: Discussionmentioning
confidence: 99%
“…However, all the aforementioned papers evaluated post-operative specimens, often including patients who had previously received NAC. It is well known that systemic therapies can potentially promote changes in biomarker expression [32]; hence, the lack of administration of prior therapies may account, at least in part, for the generally higher PT-ALN agreement rates in studies excluding patients receiving NAC [29]. To the best of our knowledge, differences in critical biomarker expression between PTs and ALN metastases in pre-operative CNBs have not been evaluated yet.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of biological changes that can occur as the cancer progresses to the nodes, though the rate at which this happens is unclear. Some studies have suggested discordance between the primary and nodal cancer happens often-more than 30% for ER, 40% for PR and 24% for HER2 [108]-and others say it is not often enough to warrant evaluating biomarkers in all positive nodes [109,110], and yet others suggest it is somewhere in between [111,112]. To definitively characterise nodal metastases, it may be necessary to evaluate the same biomarkers in cancerous nodal tissue in addition to the primary tumour, as this information could change the treatment plan for some patients.…”
Section: Discussionmentioning
confidence: 99%